Encrypted Data Toward Finance Security in Indonesia Literature Review Study - Meliala, Brandon Nathanael (Universitas Komputer Indonesia, 2025)
This study examines the role of data encryption in strengthening financial security in Indonesia through a literature review approach. Rapid growth of digital banking, fintech services, and cashless transactions has increased exposure to cyber threats such as data breaches, identity theft, and financial fraud. By synthesizing findings from national and international journals, regulations, and industry reports, this article analyses types of encryption used in financial systems, including symmetric and asymmetric algorithms, end-to-end encryption, and key management practices. The review highlights that encryption significantly reduces the risk of unauthorized access and supports compliance with regulatory frameworks on data protection and financial stability. However, challenges remain in implementation, such as limited technical capacity, high operational costs, and uneven security awareness among institutions and users. This study concludes that effective encryption strategies, combined with governance and user education, are essential to enhance trust and resilience in Indonesia’s financial sector in the long term.